Effect of packaging systems on dried shrimp quality and storage stability as visualized using pattern recognition - Siripatrawan, Ubonrat; Hwansena, Veeranuch; Ornrootee, Kamonwan; Chuesiang, Piyanan; Ruengdech, Anchalee; Keratimanoch, Sumate; Jaturontrasame, Penpimol (Agriculture and Natural Resources, 2022)
Importance of the work: Dried shrimp in a conventional polypropylene bag has a short shelf life, causing food waste and retail loss. Hence, an effective packaging system is required to maintain product quality and extend the shelf life. Objectives: To investigate the effects of different packaging systems on the quality of dried shrimp. Materials and Methods: Dried shrimp samples were packaged in four different systems: polypropylene under atmospheric air (PP), polyamide-laminated (PA) film under vacuum (PA+V), polyamide-laminated film with an oxygen scavenger (PA+OS) and aluminum-laminated film under vacuum (AL+V). The packaged dried shrimp was monitored for changes in astaxanthin, thiobarbituric acid, water activity, color, hardness and organoleptic quality during storage for 12 wk. Linear discriminant analysis (LDA) was used for pattern recognition and data classification. Results: The four types of packaging system produced different quality levels of the product. PA+OS was the best at preserving astaxanthin, retarding lipid oxidation, maintaining color and extending the shelf life of the dried shrimp, followed by AL+V, PA+V and PP, respectively. Oxygen scavenging was more effective at reducing the residual oxygen in the package than vacuum packaging. The LDA-based pattern recognition could visualize the effect of different packaging systems on the overall quality of the dried shrimp. Main finding: PA+OS provided much better protection than the other types of packaging. The longer shelf life of this product should not only motivate more sales with less retail waste but also enhance product exportation.